Twitter: a capacidade dos trending topics em pautar o debate - Silva, Igor Fediczko (2024)
This study aims to analyze the interrelationship between Twitter and mainstream media coverage during the 2022 presidential elections in Brazil. Through a focus on the programming of 4 important vehicles (Jornal Nacional, Folha de S.Paulo, Revista Veja and Jovem Pan), as well as the extraction of metrics from the platform itself, we seek to investigate to what extent the algorithmic logic and Twitter engagement metrics influenced the media framing of the campaign's central themes. It is based on the premise that the digital public arena, with its viral circulation of content and speeches, exerts appreciable agenda-setting power over the editorial directions of political journalism. Through content analysis of the material conveyed by the 4 vehicles throughout the campaign, we seek to categorize the pieces according to their content (informative, interpretative or evaluative) as well as identify correlations with trending topics, influential profiles and frames disseminated first on Twitter and then reverberated in traditional news. This investigation is anchored in Pierre Bourdieu's theoretical framework on the symbolic power of social fields and their communicative structures. Finally, by elucidating the complex processes of interinfluence between digital platforms and journalistic companies, the study aims to shed light on how particular consensuses and worldviews can acquire prominence in the public debate, to the detriment of dissident perspectives